Parallel Route to Synthesis of Triphenyl Substituted Guanidine - Singh, Lakshman; Singh, Upma; Kumar, Sudhir (Asian Journal of Chemistry, 2010)
This work presents a short and attractive method to synthesise a variety of NN′N″-triphenyl substituted guanidine in high yields.